Cover Image, Volume 173A, Number 3, March 2017. Issue 3 (March 2017) - Salian, Smrithi; Cho, Tae‐Joon; Phadke, Shubha R.; Gowrishankar, Kalpana; Bhavani, Gandham SriLakshmi; Shukla, Anju; Jagadeesh, Sujatha; Kim, Ok‐Hwa; Nishimura, Gen; Girisha, Katta M.
Abstract : The cover image, by Katta M. Girisha et al., is based on the Original Article Additional three patients with smithmccort dysplasia due to novel rab33b mutations, DOI:10.1002/ajmg.a.38064 .